Cutoff Point of HbA1c for Diagnosis of Diabetes Mellitus in Chinese Individuals - Wang, Bing (PLoS One, 2016)
BACKGROUND: The purpose of the present study was to find the optimal threshold of glycated hemoglobin (HbA1c) for diagnosis of diabetes mellitus in Chinese individuals. METHODS: A total of 8 391 subjects (including 2 133 men and 6 258 women) aged 40–90 years with gradable retinal photographs were recruited. The relationship between HbA1c and diabetic retinopathy (DR) was examined. Receiver operating characteristic (ROC) curves were used to find the optimal threshold of HbA1c in screening DR and diagnosing diabetes. RESULTS: HbA1c values in patients with DR were significantly higher than in those with no DR. The ROC curve for HbA1c had an area under the curve of 0.881 (95%CI 0.857–0.905; P = 0.000). HbA1c at a cutoff of 6.5% had a high sensitivity (80.6%) and specificity (86.9%) for detecting DR. CONCLUSIONS: HbA1c can be used to diagnose diabetes in a Chinese population, and the optimal HbA1c cutoff point for diagnosis is 6.5%.